2010
DOI: 10.1021/jp1071023
|View full text |Cite
|
Sign up to set email alerts
|

Rate Coefficients for the Gas-Phase Reaction of Hydroxyl Radicals with 2-Methoxyphenol (Guaiacol) and Related Compounds

Abstract: 2-Methoxyphenol (guaiacol) and its derivatives are potential marker compounds for wood smoke emissions in the atmosphere. To investigate the atmospheric reactivity of this type of compounds, rate coefficients for their reactions with hydroxyl (OH) radicals have been determined at 294 ± 2 K and 1 atm using the relative rate method with gas chromatography for chemical analysis. The rate coefficients (in units of cm³ molecule⁻¹ s⁻¹) are: 2-methoxyphenol, (7.53 ± 0.41) × 10⁻¹¹; 3-methoxyphenol, (9.80 ± 0.46) × 10⁻… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 22 publications
8
78
3
Order By: Relevance
“…Of these groups, activation potential of the ring increases in order of −CH 3 < −OCH 3 < −OH. Thus, as predicted, methoxyphenol compounds react faster with OH than their methyl or unsubstituted equivalents (Coeur-Tourneur et al, 2010). Methoxy and hydroxy substituent groups tend to make OH-attack favorable at positions ortho and para to the substituents, so structures for the measured ions are proposed from chemical mechanisms assuming one of these positions of initial OHattack.…”
Section: Gas-phase Oxidationmentioning
confidence: 70%
See 1 more Smart Citation
“…Of these groups, activation potential of the ring increases in order of −CH 3 < −OCH 3 < −OH. Thus, as predicted, methoxyphenol compounds react faster with OH than their methyl or unsubstituted equivalents (Coeur-Tourneur et al, 2010). Methoxy and hydroxy substituent groups tend to make OH-attack favorable at positions ortho and para to the substituents, so structures for the measured ions are proposed from chemical mechanisms assuming one of these positions of initial OHattack.…”
Section: Gas-phase Oxidationmentioning
confidence: 70%
“…Syringol vapor-phase wall loss in the reactors is also believed to be minimal. Lauraguais et al (2012) found no vapor-phase wall loss of syringol and Coeur-Tourneur et al (2010) found negligible losses for guaiacol and related methoxy and alkyl substituted benzenes. Assuming a first-order wall loss rate, k w ∼ 1 × 10 −5 s −1 , a typical rate for previously tested compounds in our chamber (Loza et al, 2010), this would lead to roughly a quarter loss of syringol to the walls over the course of the experiment.…”
Section: Soa Yieldsmentioning
confidence: 99%
“…Other significant products from burning grasses are acetosyringone, syringic acid, vanillin and vanillic acid. Methoxy phenols degrade in the atmosphere, where 2-methoxyphenol (guaiacol) and its isomers in the gas-phase react with OH hydroxyradicals (Coeur-Tourneur et al, 2010), while phenols react with 3 C ⁎ (aromatic carbonyl) and some methoxy phenols in particulate matter react with O 3 (Net et al, 2011), NO 3 (Liu et al, 2012), 3 C ⁎ , OH (Li et al, 2014;Yu et al, 2014), and UV (Li et al, 2014). Most previous determinations of PCs in aerosols were performed in zones close to residential areas using biomass burning in domestic heating (Bari et al, 2010(Bari et al, , 2011Dutton et al, 2009Dutton et al, , 2010He et al, 2010;Simpson et al, 2005;Ward et al, 2011) or else in zones heavily impacted from wildfire smoke (Ward et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A basic assumption in source apportionment models is that the tracers should have sufficient stability to persist in the atmosphere. In previous studies, particle-phase biomass burning tracers were all thought to be sufficiently stable, 35 but a few recent studies have indicated that some tracers have high reactivity to oxidizing radicals, based on chamber experiments, field observations 1,32,[36][37][38][39][40][41][42][43] and quantum chemical calculations. [44][45][46] As for DHAA, there are only limited studies which have investigated its photolysis degradation in water 47 and biodegradation in the environment by microorganisms.…”
Section: Introductionmentioning
confidence: 99%